Contemporary Psychology of Religion: Its Relevance to Education, Social Life, and Psychological Well-Being - Fitrah Muthmainnah; Salami Mahmud (LaKaspia, 2026)
The psychology of religion has expanded from a predominantly individual study of religious experience into a multidimensional field concerned with psychological, social, cultural, educational, and spiritual processes. Nevertheless, existing studies frequently examine its educational, mental health, social, and theoretical dimensions separately, resulting in limited conceptual integration across these domains. This article examines the contemporary development of the psychology of religion and synthesizes its relevance to education, social life, and psychological well-being. It employed a qualitative narrative-integrative literature review of recent publications identified through Google Scholar using Publish or Perish, supplemented by seminal works required to explain foundational concepts. The selected literature was analyzed through qualitative content analysis involving thematic coding, comparison of convergent and divergent arguments, and conceptual synthesis. The review identified three interrelated findings. First, contemporary psychology of religion conceptualizes religiosity as a dynamic and multidimensional phenomenon shaped by personal development and sociocultural contexts. Second, in education, religious meaning, moral reflection, social learning, and emotional regulation may contribute to character formation, learning motivation, psychological well-being, and social responsibility. Third, in social life, religiosity may support meaning-making, coping, prosocial behavior, tolerance, solidarity, and community support. These effects are not automatic, however, because rigid, punitive, or exclusionary interpretations may contribute to guilt, spiritual conflict, psychological distress, and social exclusion. The psychology of religion should therefore be applied critically and contextually, with attention to religious orientation, interpretation, pedagogy, social support, and cultural diversity.